URGENSI PENDIDIKAN PANCASILA DALAM MEMBENTUKKARAKTER SISWA TANGGUH MENGHADAPI TANTANGAN HOAKS DI ERA DIGITAL PADA SISWA KELAS 8 SMP NEGERI 7 KOTA SURAKARTA TAHUN 2025 - Melinda Budi Ayu; Trisiana, Anita; Siti Supeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the face of digital challenges rife with misinformation and fake news, Pancasila education is crucial in helping students develop their character. However, its use in the classroom often prioritizes knowledge over developing students' moral resilience. The purpose of this study is to examine how Pancasila education is used to help eighth-grade students at SMP Negeri 7 Surakarta City build resilient character in the face of lies in the digital age. This research employed a case study and qualitative methodology. Semi-structured interviews, participant observation, and documentation were used to collect data, which was then evaluated interactively using a triangulation approach to ensure data accuracy. According to the research findings, Pancasila education is implemented holistically through improvements in the curriculum, school culture, school policies, and learning that are relevant to contemporary situations. Students' ability to verify information, control their emotions, and understand the social impact before sharing knowledge is an indicator of their resilience. In summary, Pancasila education provides a flexible framework and moral foundation for digital citizenship. It is recommended that schools and families continue to collaborate to improve the integration of digital literacy.